2018
DOI: 10.3233/nre-172273
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation paired with tactile training improved sensory function in a chronic stroke patient

Abstract: BACKGROUND:Recent studies indicate that vagus nerve stimulation (VNS) paired with rehabilitation can enhance neural plasticity in the primary sensory and motor cortices, improve forelimb function after stroke in animal models and improve motor function in patients with arm weakness after stroke. OBJECTIVE:To gain "first-in-man" experience of VNS paired with tactile training in a patient with severe sensory impairment after stroke. METHODS:During the long-term follow-up phase of a clinical trial of VNS paired w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 22 publications
3
36
1
Order By: Relevance
“…Subsequently, Kilgard et al reported sensory improvements in a stroke survivor who received VNS (via a surgically implanted stimulator) paired with a sensory stimulus ('tactile therapy') of the upper limb [8]. The individual was asked to localise, identify and explore a variety of everyday objects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Kilgard et al reported sensory improvements in a stroke survivor who received VNS (via a surgically implanted stimulator) paired with a sensory stimulus ('tactile therapy') of the upper limb [8]. The individual was asked to localise, identify and explore a variety of everyday objects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral nerve stimulation has emerged as a means to treat a variety of neurological diseases including pain, sleep apnea, urinary incontinence, stroke, and tinnitus [1][2][3][4][5][6][7][8][9][10][11]. Given the broad application of the potential therapy, there is a great deal of interest in developing improved technologies to deliver nerve stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with recent studies exploring the potential of combined VNS and physical training for stroke rehabilitation. For example, Kilgard and colleagues found that invasive VNS stimulation delivered at 30 Hz was associated with improved somatosensory function in a patient with severe sensory impairment due to stroke [14]. Similarly, a study of twelve stroke patients that received auricular VNS at 25 Hz during performance of a motor task found that most patients showed post-intervention increases in sensory function [8].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty (20) subjects were randomly assigned to each of four stimulation frequency groups (30Hz, 300Hz, 3kHz, or sham). Thirty (30) Hz stimulation was chosen because frequencies in this range are associated with high degrees of cortical plasticity changes in animal experiments [13] and have been used in previous studies of stroke patients [8,14]. Higher frequencies were included based on their use in other cranial nerve studies [9,15] and observations that these frequencies Figure 2.…”
Section: B Stimulation Protocolmentioning
confidence: 99%